Evaluation of Cucumber Hybrids for Yield and Quality Under Plastic House and Open Field Conditions - Gautam, Ishwori Prasad; Pradhan, Navin Gopal; Subedi, Sujan; Thakur, Manis Kumar (Nepalese Horticulture, 2021)
Low yield of off-season cucumber due to use of open-pollinated varieties with high male to female ration, long gestation period and high incidence of diseases are the major problems of cucumber production in Nepal. The use of imported hybrids varieties during the off-season and plastic film technology has shown to lead to enhanced growth and higher yield in recent years. However, there is a little work on hybrid cucumber research and their testing in Nepal. Therefore, experiments were conducted at the National Horticulture Research Center (NHRC), Directorate of Agricultural Research (DoAR), Tarahara and Farmer's field in Dhankuta district accordingly to select best hybrids. Sixteen genotypes including best Indian hybrid Dynasty and 3 open-pollinated check genotypes were evaluated at NHRC, Khumaltar during the years 2018 and 2019 in Randomized Complete Block Design (RCBD) with three replications under the plastic house. Previously selected seven genotypes were evaluated in DoAR, Tarahara in 3 replications and best hybrid was compared with farmers' varieties in Dhankuta at open field conditions. Tested genotypes showed a significant difference in yield and other parameters like male to female ratio, early flowering, vine length, disease scoring etc. both under the plastic house and open field conditions. The new hybrids HRD CUM 009 x 003 (107.05 mt/ha), HRD CUM 006 x 003 (91.55 mt/ha) and HRD CUM 004 x 001(88. 10 mt/ha) were promising due to higher yield, earlier to 50% female and male flowering, a greater number of female flowers, short vine length, higher number of fruits per plants and earliness harvesting than other cultivated varieties. Most of the tested hybrids produced more than double yield than open-pollinated genotypes.